Qualitative research in understanding effects of mobile technology use in worker-leader relationships - Olund, Judith G (ProQuest Dissertations & Theses, 2012)
The purpose of this qualitative study with a narrative inquiry research design was to explore in what way mobile technology use strengthens or weakens worker-leader relations. Research findings indicated that the advantages of mobile technology use outweigh disadvantages. Semi-structured researcher-subject open-ended interviews reflected worker and leader perspectives generating 164 pages of textual data for interpretive analysis through context coding, text categorization, inductive analysis, interpretive assessment, and Microsoft Excel© software. Seventeen formative themes developed: (a) Leaders find communication through mobile technology appropriate; (b) Leaders find mobile technology has an appropriate effect on workers; (c) Leaders find mobile technology has an appropriate effect on workers and information; (d) Leaders find that mobile technology facilitates work; (e) Workers find that mobile technology facilitates work; (f) Workers find that mobile technology is an information mechanism; (g) Workers find mobile technology as a channel; (h) Workers find mobile technology fosters different effects; (i) Mobile technology is necessary for communication; (j) Mobile technology is necessary in facilitating worker-leader relationships; (k) Mobile technology is an information mechanism for worker-leader relationships; (l) Mobile technology is a channel used for worker-leader relationships; (m) Mobile technology affects workers in worker-leader relationships; (n) Mobile technology fosters different effects in worker-leader relationships; (o) Mobile technology is a channel that enhances transactional leadership; (p) Mobile technology facilitates transformational leadership; and (q) Mobile technology affects workers through enhanced charismatic leadership.